The correlation between serum 25-hydroxyvitamin D level and ulcerative colitis: a systematic review and meta-analysis - Liu, Chenyu; Liu, Xin; Shi, Haitao; Chen, Fenrong; Sun, Linlang; Gao, Xin; Wang, Yan (European journal of gastroenterology & hepatology, 2023)
The incidence of UC has increased yearly. Many studies have suggested that patients with ulcerative colitis have abnormal vitamin D levels. A systematic review and meta-analysis were conducted to investigate the association between vitamin D levels and ulcerative colitis. We searched PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, Wanfang and China Science and Technology Journal Database (VIP) from inception to December 2022. We included case-control studies comparing the differences in vitamin D levels between patients with ulcerative colitis and healthy populations. Meta-analysis was performed using Review Manager5.4, Stata17.0 and other software. Sixteen eligible observational studies were selected from 473 articles involving 2234 subjects, and they included 987 patients with ulcerative colitis and 1247 controls. The results showed that the serum level of vitamin D in patients with ulcerative colitis was significantly lower than that in healthy controls (SMD = -0.83, 95% CI: -1.18, -0.48). Vitamin D deficiency was reported in five studies. The prevalence of vitamin D deficiency was significantly higher in the ulcerative colitis group than in the healthy control group (OR = 1.90, 95% CI: 1.38, 2.62). Serum vitamin D levels were significantly lower in patients with ulcerative colitis than in healthy controls.